Die Niederschlagsverhältnisse im Südwesten der Arabischen Halbinsel.: Ein Beitrag zum Klima des Nordjemen - Remmele, Gerhard (ERDKUNDE, 1989)
So far, investigations on the climate of South-west Arabia could not be pursued for the lack of sufficient data. In this article, the author seeks to characterize the climate, specifically the rainfall conditions of the south-western of the Arabian Peninsula, on the basis of slightly improved yet still not satisfactory data. Three rainfall profiles - of the Tihama coastal region up to the Yemen Highlands, of the Tihama of Saudi Arabia and North Yemen, and of the highlands of both countries - show similarities and differences concerning the absolute rainfall amount and the rainfall regimes in dependence upon different climatic factors. The regularities found are interpreted on a genetic-dynamic basis, taking into consideration the respective state of research. This results in congruences with dominating concepts, as well as in discrepancies, which will require further explanations.